Soldiers' perspectives of the Married Army Couples Program: A review of perceived problems and proposed solutions. Issue 4 (4th July 2018) - Huffman, Ann Hergatt; Dunbar, Nora; Broom, Timothy W.; Castro, Carl A.
ABSTRACT: The current study investigated soldiers' perceptions of the Married Army Couples Program (MACP) using data from focus groups conducted with Army personnel in dual-military marriages. Despite the high success rate of the program (approximately 80–83%)—success being defined as establishment of a joint domicile within a 50-mile radius of each spouse's duty station—a variety of difficulties were reported as well as consequent negative perceptions. Problems included dissatisfaction with the parameters defining joint domicile, obstacles to career advancement, lack of quality information regarding the program, and unequal allocation depending on one's level of leadership support. Difficulties with MACP led to negative impressions of the program and of the Army as a whole. Specifically, when asked about challenges related to the program, many participants reported perceptions of a poorly functioning program, an uncaring environment, and of the Army as a hypocritical institution. For individuals in dual-military marriages, these difficulties affect quality of life. For the institution, these negative perceptions can potentially lead to problems with retention of one or both members of a dual-military couple. We propose several strategies to improve the effectiveness of MACP and to increase positive perceptions of the program based on suggestions from the focus groups in addition to the military and work literatures.